2019
DOI: 10.1021/acsapm.8b00085
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Poly(oligoethylene glycol methacrylate)-Based Hydrogels Fabricated from Highly Branched Precursor Polymers: Controlling Gel Properties by Precursor Polymer Morphology

Abstract: The physicochemical properties of injectable hydrogels are typically modified by altering the chemistry of the precursor polymer and/ or the amount or type of cross-linker, both of which can lead to hydrogels with altered mechanics, swelling, degradation, and other key physical properties. Herein, we describe an alternative approach to tune the properties of injectable hydrogels (here, based on hydrazone cross-linked poly(oligoethylene glycol methacrylate), or POEGMA) by altering the architecture of the precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Alternatively, by preparing hyperbranched hydrazide and/or aldehyde-functionalized POEGMA precursor polymers with different ratios of cross-linker (ethylene glycol dimethacrylate) and chain transfer agent (2-cyano-2-propyl 4cyanobenzodithioate) to control the degree of branching, we showed that precursor polymers with higher degrees of branching promoted stiffer gel mechanics due to the effective "pre-crosslinking" inside the hyperbranched polymer precursor itself. 30 Interestingly, a combination of one hyperbranched polymer and one linear polymer demonstrated the stiffest mechanics (6-fold stronger than the all-linear system and 2fold stronger than the all-hyperbranched system) but with the same gelation time (∼10 min) as the weaker all-hyperbranched system. We attributed this result to the lower conformational mobility of the cross-linkable groups in the all-hyperbranched system.…”
Section: Reinforcement Strategies For In Situmentioning
confidence: 96%
See 2 more Smart Citations
“…Alternatively, by preparing hyperbranched hydrazide and/or aldehyde-functionalized POEGMA precursor polymers with different ratios of cross-linker (ethylene glycol dimethacrylate) and chain transfer agent (2-cyano-2-propyl 4cyanobenzodithioate) to control the degree of branching, we showed that precursor polymers with higher degrees of branching promoted stiffer gel mechanics due to the effective "pre-crosslinking" inside the hyperbranched polymer precursor itself. 30 Interestingly, a combination of one hyperbranched polymer and one linear polymer demonstrated the stiffest mechanics (6-fold stronger than the all-linear system and 2fold stronger than the all-hyperbranched system) but with the same gelation time (∼10 min) as the weaker all-hyperbranched system. We attributed this result to the lower conformational mobility of the cross-linkable groups in the all-hyperbranched system.…”
Section: Reinforcement Strategies For In Situmentioning
confidence: 96%
“…Similar overall results were achieved in “click” cross-linked hydrogels formed based on linear PEG precursor polymers functionalized with orthogonal alkyne or azide groups; doubling the number of azide groups (and thus the cross-link density) resulted in stiffer hydrogels, while an intermediate PEG molecular weight (10 kDa versus 4.6 and 20 kDa) led to hydrogels with highest Young’s modulus due to the balance between chain-end reactivity (increased with higher chain flexibility i.e., molecular weight) and the distance between cross-link sites. Alternatively, by preparing hyperbranched hydrazide and/or aldehyde-functionalized POEGMA precursor polymers with different ratios of cross-linker (ethylene glycol dimethacrylate) and chain transfer agent (2-cyano-2-propyl 4-cyanobenzodithioate) to control the degree of branching, we showed that precursor polymers with higher degrees of branching promoted stiffer gel mechanics due to the effective “pre-crosslinking” inside the hyperbranched polymer precursor itself . Interestingly, a combination of one hyperbranched polymer and one linear polymer demonstrated the stiffest mechanics (6-fold stronger than the all-linear system and 2-fold stronger than the all-hyperbranched system) but with the same gelation time (∼10 min) as the weaker all-hyperbranched system.…”
Section: Reinforcement Strategies For In Situ Gelling Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, they reported that the architecture of the precursor polymers (branching) could be used to tune the properties of injectable hydrogels. 37 Hydrogels prepared using highly branched precursor polymers possessed faster gelation and higher stiffness than hydrogels prepared with linear precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique structure and superior performances, methacrylate-based monomers and polymers have attracted much attentions [1][2][3], especially for the fluorinated ones. For example, it was reported that fluorinated methacrylate polymers have excellent surface properties, impressive optical performances [4,5] and thus are extensively applied in the fields of ice-phobic coatings, functional thin film, medical materials, optical devices/fiber and nanocomposites [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%